An Analysis of Writing Problems of PGSD Unnes Students - Arif Widagdo (Universitas Muhammadiyah Semarang, 2017)
Writing is considered a productive skill and useful tool for learning process. It is the most used skill in evaluating students performance in almost all levels of education. In Indonesia, tertiary level students still face enormous writing problems in English. The objective of this present study aims to explore writing problems of students of PGSD (Primary School Teacher Education) Department, Faculty of Education, Semarang State University (UNNES), and the study is also intended to share some recommendations how students can get overcome those problems. The study was conducted on 160 students of PGSD UNNES from the same level. The data were taken through document collection and questionnaire. Moreover, a semi-structured interview on two lecturers has been conducted to reflect their attitudes and opinion on students English writing problems. The results of this study showed that students face many problems when writing English. The problems could be classified into some categories. In addition, a few recommendations are provided on the basis of the result. This study could help the teachers/lecturers to resolve the problems and find some strategies to improve students writing in English.